Teori Filter Bubble dan Echo Chamber: Dampak Transformasi Digital Terhadap Pendidikan Islam - Salman Shiddiq; Misra Misra (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
Digital transformation has brought significant changes to education, revolutionizing the way knowledge is accessed, shared, and disseminated. It has provided a wealth of opportunities for innovation, convenience, and accessibility in learning. However, the rapid shift to digital platforms presents several challenges that may hinder the development of students’ critical thinking and exacerbate educational inequalities. Among these challenges are the digital divide, filter bubbles, and echo chambers, which can negatively impact students’ perspectives and deepen the educational gap between urban and rural areas. This research aims to analyze the effects of digital transformation on education, with a particular focus on Islamic education. It also explores the role of filter bubbles and echo chambers in shaping students' insights and understanding of various issues. The research method used is library research, involving the collection and analysis of literature from various scholarly sources such as Sinta, ResearchGate, and Google Scholar. The findings of the study highlight that digital transformation has facilitated the learning process through platforms like Google Classroom and Zoom, making education more accessible. However, it also introduces challenges, such as the spread of misinformation and hoaxes, which are amplified by filter bubbles and echo chambers. From an Islamic educational perspective, digital transformation aligns with the principles of seeking knowledge and justice. However, the digital divide contradicts the Islamic value of equal access to education for all. In conclusion, it is necessary to improve digital literacy, provide equitable infrastructure, and promote cross-perspective collaboration to create a more inclusive and equitable learning environment. The findings aim to guide policymakers and educators in shaping better educational strategies.